The Effect of Multimodal Texts on Studentsâ Reading Comprehension - Astarilla, Liya; Warman, Dede (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research aimed to know the effect of multimodal texts on studentsâ reading comprehension ability. This was an experimental research. The participants of this research consisted of 60 students of the second semester at a private college in Pekanbaru in the academic year of 2016/2017, 30 students were assigned as experimental group and another 30 students as control group. The instrument of this research was reading comprehension test in form of multiple choices, used as pre-test and post-test to asses the participantsâ reading comprehension ability in both experimental and control group. The result of this research found that there was significant effect in the post-test after using multimodal text in learning reading comprehension in experimental group. It was obtained that the value of t-test was 4.223 while the value of t-table was 2.002, with the level of significant Î± = 0.05 at 58 degrees of freedom. The t-test result was higher than the value of t-table, therefore the hypothesis HÄ± was accepted. The research concludes that there was significant effect of multimodal text on studentsâ reading comprehension.